A note on the seasonality of stock returns on the Johannesburg Stock Exchange - D. J. Bradfield (South African Journal of Business Management, 1990)
Evidence from studies on the major stock exchanges world-wide suggests that stocks listed on these markets earn abnormally high returns in the month of January. In this article the seasonality of stocks on the Johannesburg Stock Exchange is empirically investigated. Surprisingly no January effects are found, however, a significant December seasonal effect is documented. A plausible explanation for this finding is offered.
Keywords: 650